HARMS OF CERVICAL CANCER SCREENING IN THE UNITED STATES AND THE NETHERLANDS - Habbema, Dik (Int J Cancer, 2017)
We studied harms related to cervical cancer screening and management of screen-positive women in the United States (US) and the Netherlands. We utilised data from four US integrated health care systems (SEARCH), the US National Health Interview Survey, New Mexico state, the Netherlands national histopathology registry, and included studies on adverse health effects of cervical screening. We compared the number of Papanicolaou (Pap) smear tests, abnormal test results, punch biopsies, treatments, health problems (anxiety, pain, bleeding, and discharge), and preterm births associated with excisional treatments. Results were age-standardized to the 2007 US population. Based on SEARCH, an estimated 36 million Pap tests were performed in 2007 for 91 million US women aged 21–65 years, leading to 2.3 million abnormal Pap tests, 1.5 million punch biopsies, 0.3 million treatments for precancerous lesions, 5 thousand preterm births, and over 8 million health problems. Under Netherlands screening practice, fewer Pap tests (58%), abnormal test results (64%), punch biopsies (75%), treatment procedures (40%), preterm births (60%), and health problems (63%) would have occurred. The SEARCH data did not differ much from other US data for 2007 or from more recent data up to 2013. Thus compared with the less intensive screening practice in the Netherlands, US practice of cervical cancer screening may have resulted in two- to three-fold higher harms, while the effects on cervical cancer incidence and mortality are similar. The results are also of high relevance in making recommendations for HPV screening. Systematic collection of harms data is needed for monitoring and for better incorporation of harms in making screening recommendations.